ISLAMIC FINANCE AND DEVELOPMENT PROSPECTS IN MODERN CONDITIONS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article examines the concept and essence of Islamic finance, consistent with the principles of Sharia, and its practical application, the development of the Islamic economy, the donation of international financial institutions and Islamic banks in the formation of banking resources. The role and importance of the development of Islamic finance in the process of transformation of the financial and banking system are also considered. The perspective of the development of Islamic finance and its role in the development of the country's economy is considered. Suggestions and recommendations on the implementation of the principles of Islamic finance are given.